Data protection practices of selected student organizations in the University of the Philippines Diliman - Tagle, Paul Jorge I.
In the digital age, where potential data risks are more severe than ever, necessitating higher levels of accountability and data security, especially within non-juridical entities, this study aimed to examine the data protection practices of student organizations in the University of the Philippines Diliman. The study concentrated on the four fundamental dimensions of individuals' concerns regarding organizational information privacy: collection, secondary use, error, and improper access. Utilizing a qualitative method, data were gathered from student organizations in the university that were not registered with any legal personality-granting bodies, through modified surveys and semi-structured interviews. Qualitative coding method was employed to interpret the data, focusing on key concepts that emerged from the surveys and interviews. The findings can provide a foundation for developing tailored legal frameworks that promote responsible data management and protection within this specific context.